ASPEK LEGALITAS CAGAR BUDAYA PURA DALEM SOLO DI DESA SEDANG KECAMATAN ABIANSEMAL - Wijayanti, Eva; I Made Adi Widnyana; I Made Suta (VYAVAHARA DUTA, 2025)
Dalem Solo Temple Located in Medium Village, Abiansemal District, is generally used as a place of worship for Hindus, has a lot of history and has the potential to become an excellence. However, if it is not managed creatively and innovatively, this will be a threat to the Cultural Heritage. Management efforts through the preservation of Cultural Heritage must be carried out carefully based on basic concepts in the form of master plans and detailed implementation documents to anticipate deviations when implementing future strategies. Dalem Solo Temple is a Cultural Heritage under the guidance of the Bali Archaeological Preservation Center. Based on this description, the problem will be studied through  Objectives, including: To Know and Analyze the Legality Aspects in Preserving the Cultural Heritage of Dalem Solo Temple in Sedang Village.  The research was studied using empirical legal research methods that used legal theory, namely legal protection theory and supervision theory. The results of the study show that community participation in the village is included in the free category, meaning that seen from the degree of volunteerism, the way of involvement in various stages of the development process involves themselves directly without being represented in community activities. The legality of the Cultural Heritage of Dalem Solo Temple is under the guidance of the Bali Archaeological Heritage Preservation Center.1) Dalem Solo Temple which is based on the Decree of the Head of the Bali Archaeological Heritage Preservation Center in the Working Area of the Province of Bali, NTB and NTT Number: HK.501/06/UPT/DKP/2007 concerning the Determination of Cultural Heritage Objects. 2) Letter of Determination of Cultural Heritage Objects, Number: HK.501/07/UPT/DKP/2007 Decree of the Badung Regency Cultural Office.